Use of etymology in the teaching and learning of biological and taxonomic concepts of Chilean native fauna - Fuentealba-Cruz, Marta (2024)
Objective. Evaluate the impact of a didactic sequence, incorporating the use of the etymology of biological taxonomic concepts in the acquisition of knowledge about the Chilean native fauna. Methodology. To carry this out, the brief conceptualization technique (one-minute paper), the metacognitive self-assessment scale instrument known as the Knowledge and Prior Study Inventory (KPSI), a knowledge test, as well as an open question test were applied to 42 third year high-school students, before and after implementing the sequence remotely. Results. From the analysis of the results, a lexical diversity value (TTR) of 0.398 and 0.421 was obtained before and after the intervention, respectively. On the other hand, significant differences (p < 0.001) in the students´ level of knowledge were detected before (8.5 points) and after (11.4 points) the didactic implementation. This suggests that the use of the etymology of biological taxonomic concepts contributed to the students’ increase in vocabulary and level of knowledge about the Chilean native fauna by incorporating the characteristics of these animals into their cognitive repertoire, promoting the development of scientific skills such as deep understanding of concepts and deduction, in addition to encouraging interest and motivation in the conservation of this fauna and its environment. Conclusion. It can be concluded that it is advisable to incorporate etymology systematically in the teaching of different biological subjects at high-school level, since it contributes to increasing the scientific literacy of secondary students.